A Review on “The Three Laws of Performance” and Landmark Education - Azgın, Bilge (Journal of History Culture and Art Research, 2018)
This article aims to scrutinize and expose the contextual link between The Three Laws of Performance: Rewriting the Future of Your Organization and Your Life and the Landmark Worldwide (or simply Landmark). Enriched with numerous real-life examples from around the world, “The Three Laws of Performance” is an original and rare contribution to the field as it exposes the fundamental distinctions and transformative technologies offered by the Landmark courses to its readers. While reviewing the content of the book, the article also automatically elucidates the critical distinctions provided by Landmark such as “change versus transformation”, “possibility”, “racket”, “internal voice”, “completing the past”, “default future”, “generative language”, “rewriting future”, “life sentence”, “ontological leadership”, and “authenticity”. In spite of its certain critical shortcomings, “The Three Laws of Performance” deserves credit for originally and powerfully subsuming many of the various distinctions taught in Landmark courses under the axiomatic principles dubbed “the three laws of performance.”